Neutrosophic Vague Generalized Pre-Closed Sets in Neutrosophic Vague Topological Spaces - A. Mary Margaret; M. Trinita Pricilla (International Journal of Mathematics And its Applications, 2017)
The aim of this paper is to introduce and develop a new class of sets namely neutrosophic vague generalized pre-closed sets in neutrosophic vague topological space. Further we have analyse the properties of neutrosophic vague generalized pre-open sets. Also some applications namely neutrosophic vague T_1/2 space, neutrosophic vague _pT_1/2 space and neutrosophic vague _gpT_1/2 space are introduced.